Karakterisasi Senyawa Hasil Isolasi dari Ekstrak Etil Asetat Daun Namnam (Cynometra Cauliflora L.) yang Memiliki Aktivitas Antibakteri - Tiah Maharani; Dede Sukandar; Sandra Hermanto (Syarif Hidayatullah State Islamic University, 2016)
Namnam is known as a plant family of fabacea that contains phenolic compounds with diverse biological activities including antibacterial. The aim of this study was to isolate and characterize the antibacterial activity of compounds isolated from ethyl acetate extract of the leaves namanam (Cynometra cauliflora L.). Extraction was done by maceration, fractionation by column chromatography, antibacterial essay by disc diffusion method, and characterization of compounds with UV-Vis, FTIR spectroscopy and LCMS. Ethyl acetate extracts have antibacterial activity with inhibition zone respectively 12.25 and 6.00 mm to Escherecia coli and Stapilococcus aureus at a concentration of 100,000 ppm. The results of column chromatography fractions 23-30 yielded three isolates with Rf 0.20 cm; 0.33 cm and 0.87 cm. Characteristics of antibacterial active compounds in isolates 2 (Rf 0.33 cm) is based on the analysis results are UV-Vis absorption at λmaks 206.93 nm, 268.40 nm, 328.58 nm, 383.98 nm and 386.98 nm , FTIR (KBr) showed -OH group 3415.68 cm-1, CH 2958.10 cm-1, C = C aromatic 1651.18 cm-1, C-OH cyclic 1019.88 cm-1 and CH aromatic 694.56 cm-1 and LCMS produce three main peak at a retention time of 4.82; 6.87 and 7.64 which is thought to be the compound 2-isopropyl-5-metilsikloheksil 2-hidroksipropanoat, Cuelure, and 2-[(2-Hydroxycyclohexyl) oxy] cyclohexanecarboxylate. Key word: antibacterial, disc diffusion, Namnam (Cynometracauliflora L.). DOI: http://dx.doi.org/10.15408/jkv.v2i1.3084